Gait energy expenditure in children with Duchenne muscular dystrophy: case study - Mariana Angélica de Souza; Marília Ester Ferreira; Cyntia Rogean de Jesus Alves de Baptista; Ana Claudia Mattiello Sverzut (Universidade de São Paulo, 2014)
This case study aimed to verify the model of Rose et al.1 as a feasible to assess energy expenditure in gait of children with Duchenne muscular dystrophy (DMD). Three DMD patients aged 6, 7 and 8 years old participated of this study. It was obtained weight, height, leg length measurement (LLM), resting and gait heart rate (HR) held on as 55-meter oval circuit performed during a two-minute test at each speed. Energy expenditure was calculated using the HR. It was performed a descriptive analysis (average) and these were compared, individually, to normative data. The average gait speed of these three patients was similar to the normative data for slow speed and lower considering comfortable and fast speed. The energy expenditure to slow speed of the patients 2 and 3 was similar to the normality, and lowest for patient 1; at comfortable speed, the energy expenditure obtained for all patients was similar; at fast speed, the patients 1 and 2 presented similar to normal values, but the patient 3 presented higher energy expenditure. It was concluded that the energy expenditure evaluation using HR was easily executed in the clinical practice and it can help therapeutic choices. For patient 3, an aerobic training could be indicated and for the others, they could keep the routine assessments.